2021
DOI: 10.1038/s41598-021-82662-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimated seroprevalence of SARS-CoV-2 antibodies among adults in Orange County, California

Abstract: Clinic-based estimates of SARS-CoV-2 may considerably underestimate the total number of infections. Access to testing in the US has been heterogeneous and symptoms vary widely in infected persons. Public health surveillance efforts and metrics are therefore hampered by underreporting. We set out to provide a minimally biased estimate of SARS-CoV-2 seroprevalence among adults for a large and diverse county (Orange County, CA, population 3.2 million). We implemented a surveillance study that minimizes response b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
2
39
2
Order By: Relevance
“…A study in Mumbai from February 2021 showed that seroprevalence in non-slums was 16.1%, while it was as high as 54.1% in slums (32). Furthermore, recent individual studies from late 2020 and early 2021 have shown seroprevalence ranging from 0.09% to 22.2% (33)(34)(35)(36)(37)(38). Some of these studies have used a Bayesian approach for accounting for misclassification bias, which represents more properly the data obtained in these seroprevalence studies (35,36).…”
Section: Seroprevalencementioning
confidence: 99%
“…A study in Mumbai from February 2021 showed that seroprevalence in non-slums was 16.1%, while it was as high as 54.1% in slums (32). Furthermore, recent individual studies from late 2020 and early 2021 have shown seroprevalence ranging from 0.09% to 22.2% (33)(34)(35)(36)(37)(38). Some of these studies have used a Bayesian approach for accounting for misclassification bias, which represents more properly the data obtained in these seroprevalence studies (35,36).…”
Section: Seroprevalencementioning
confidence: 99%
“…In this study, we compared antibody responses induced afterSARS-CoV-2 natural exposure with the responses induced by the mRNA vaccines. Pre-vaccine natural exposure data was obtained from two large serial cross-sectional surveys of residents from Orange County and the city of Santa Ana, CA, [10] and from mRNA vaccinated healthcare workers at the UCI Medical Center participating in an aggressive vaccination campaign. Within weeks of administration, the mRNA vaccines induced higher Ab levels against spike proteins than observed after natural exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Finger stick blood collection enables large scale epidemiological studies to de ne the risk of exposure to SARS-CoV-2 in different settings. [10] Since the assay requires 1 microliter of blood it is also practical for monitoring immunogenicity in neonates, children and small animal models.…”
Section: Introductionmentioning
confidence: 99%
“…We then calculated the prevalence of SARS-CoV-2 test positivity by ethnicity and employment category as well as prevalence ratios and 95% confidence intervals (CI) for each employment category. We specified our analysis specifically among those of Hispanic heritage given the notable disparities reported among that population [ 3 , 13 ], and the notable proportion of individuals of Hispanic heritage in Los Angeles [ 11 ]. The Mass General Brigham institutional review board deemed the analysis of de-identified data did not constitute human subjects’ research (2020P003530).…”
Section: Methodsmentioning
confidence: 99%